Efektivitas Nyanyian Tradisional : Ma’kaaruyen Sebagai Refleksi Makna Hidup Rakat Minahasa - Brek, Yohan; Rumate, Charga Jofial; Bokko, Lanny Sonia; Retor, Esther Avilita; Mumek, Immanuela Juliana (PADAMARA: Jurnal Psikologi dan Sosial Budaya, 2024)
The Minahasa community is known for its fondness for singing or vocal music. The song that has become the identity of the Minahasa community is known as Ma'kaaruyen. This research explores how the Minahasa community's way of life is interpreted through the song Ma'kaaruyen; a traditional musical artwork originating from Minahasa. Ma'kaaruyen is assumed to be one of the arts that reflects the life of the Minahasa community. Through a qualitative descriptive approach and analysis of the text found in the Ma'kaaruyen song, it was found that it contains meanings that integrate with the values of the Minahasa community's way of life. The musical elements in Ma'kaaruyen reflect the character and nature of traditional Minahasa society, which are associated with simplicity, tranquility, gentleness, cooperation (mapalus), and a loving attitude towards others. The extramusical meaning of Ma'kaaruyen from its lyrics is that Ma'kaaruyen is a song that conveys religious messages, advice, love, and expressions of the heart (lamentation and regret). Thus, the Ma'kaaruyen song has a reconciling function, which includes four main aspects of living in peace: a) reconciling with Allah, b) reconciling with oneself, c) reconciling with fellow human beings, and d) reconciling with the environment.